IMPACT OF MATERNAL REARING DENSITY ON LIFE HISTORY TRAITS OF MYTHIMNA SEPARATA (WALKER) - Abdul Waheed Solangi; Yunxia Cheng; Lei Zhang; Xingfu Jiang (Journal of Animal and Plant Sciences, 2025)
Migratory insects employ various adaptive strategies during alterations in the maternal environment, such as maternal rearing (Isolation, moderate, or crowding) which significantly affect their offspring's survival, development, reproduction, and onset of migration. While previous studies have mainly concentrated on the impact of varying temperature conditions on insect populations, the effects of changes in maternal rearing density on their progeny have been given relatively less attention. The current study emphasizes the impact of maternal rearing density on the offspring's life history traits in the Mythimna separata. Eggs were collected from laboratory stock and newly hatched larvae from maternal design split into three density regimes and reared at densities of low-density (LD) 1 larva, moderate density (MD) 10 larva, and high density (HD) 20 Larva per 800-ml jar with the diameter of 10cm. For initiation of the next generation, 400 females were selected from the maternal design and kept per combination for offspring larval density, eggs laid by mothers were collected and offspring were again divided into three groups and exposed to (LD), (MD), and (HD). Results demonstrated that the development time of offspring was shortened (31.62±1.14 days) after maternal high-density rearing with a significant difference, offspring’s pupal mass significantly decreased (211±7.58 mg) at stressed conditions. Low-density reared mothers laid fewer eggs (480±28.63) as compared to crowded mothers (718±45.52) eggs with significant differences. Offsprings whose mothers were raised at moderate density displayed the greatest, and offspring raised in isolation had the poorest flight capability relative to high density. Maternal larval density had a significant impact on the offspring pre-oviposition period (POP), offspring with longer POP usually showed more significant flight potential, also POP of all offspring density regimes had an essential and positive correlation with total flight distance, LD (P=0.001; R2=0.99), MD (P=0.002; R2=0.99) and HD offspring’s (P=0.001; R2=0.98). However, moderate and high-density offspring negatively correlated with total flight duration (R2-0.43) and (R2-0.48), respectively. In conclusion, the maternal rearing environment imposes phenotypic changes on offspring life history traits, and flight-induced changes in maternal egg provisioning had direct consequences for offspring growth and survival across each life stage from egg to adulthood.
Keywords: Maternal effect; density; offspring development; reproductive plasticity; flight performance